Influence of amino acid supplementation on capillary growth in the heart and skeletal muscles - Junichi Suzuki (Japanese Society of Physical Fitness and Sports Medicine, 2013)
In recent years, many experiments have investigated the impact of dietary amino acid supplementation on improvements in muscle strength and endurance capacity. However, it is unclear whether this supplementation causes vascular remodelling in skeletal muscle. This review focused on the effects of L-arginine and/or L-ornithine supplementation on capillary growth in cardiac and skeletal muscles. Although the chronic administration of 4% L-arginine did not improve capillarization in rat cardiac and hind-leg muscles, it facilitated exercise-induced capillary growth via vascular endothelial growth factor (VEGF) protein upregulation. In middle-aged rats, moderate intensity endurance training for 6 weeks did not cause capillary growth, whereas training with L-arginine supplementation led to an improvement in capillarization in the hind-leg muscle and left ventricle by promoting VEGF and endothelial nitric oxide synthase (eNOS) protein expression. The administration of L-arginine and L-ornithine for 6 weeks caused a marked increase in capillarization in rat skeletal muscle via the downregulation of endostatin and upregulation of VEGF-R2 protein expression. Moreover, this supplementation facilitated exercise-induced improvements in capillarization in the hind-leg muscles via the downregulation of endostatin and upregulation of VEGF and eNOS protein levels. The evidence presented in this review indicates that L-arginine and/or L-ornithine administration may facilitate capillary growth and endurance exercise capacity. Furthermore, this supplementation may be a useful therapeutic intervention for ischemic-related diseases.